Effect of washing treatment on the quality characteristics of white button mushroom (Agaricus bisporus) - Singh, Neha; Vaidya, Devina; Mishra, Vigya (Mushroom Research, 2015)
The edible mushroom (Agaricus bisporus) are mainly marketed in fresh form due to its highly perishable nature as it deteriorates within a few days after harvesting due to its high respiration rate and delicate epidermal structure. The present study was conducted to extend the shelf life of button mushroom. The freshly harvested mushrooms were washed with different solutions of CaCl2, citric acid, KMS and NaCl and analyzed for best washing treatment. The mushroom washed in 0.5 %KMS + 0.5 % NaCl + 0.5 % CaCl2 Â solution for 2 min had beneficial effect on the quality of mushrooms as it was found to be the best with respect to colour, texture as well as itsÂ nutritional composition.